2010
DOI: 10.1007/s00404-010-1783-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of anesthesiological strategies on neonatal bilirubin levels during cesarean section: a prospective and randomized trial

Abstract: EA and SA at cesarean section seem to be better among the four anesthesia techniques considering neonatal hyperbilirubinemia. Our findings are consistent with the idea that anesthesia may be a risk factor for hyperbilirubinemia. Although anesthesia may not significantly increase the need for interventions such as phototherapy, it may increase the burden of time, labor and cost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 15 publications
3
5
0
1
Order By: Relevance
“…The present study showed significantly higher bilirubin levels in group of general anaesthesia compared to the group where mothers received spinal anesthesia ( P <0.001). This is in agreement with the Turkish study by Demiraran et al 11) ; where significantly higher direct bilirubin levels at 5th day in the total intravenous anesthesia (TIVA) group compared to spinal anesthesia group.…”
Section: Discussionsupporting
confidence: 93%
“…The present study showed significantly higher bilirubin levels in group of general anaesthesia compared to the group where mothers received spinal anesthesia ( P <0.001). This is in agreement with the Turkish study by Demiraran et al 11) ; where significantly higher direct bilirubin levels at 5th day in the total intravenous anesthesia (TIVA) group compared to spinal anesthesia group.…”
Section: Discussionsupporting
confidence: 93%
“…Spinal anesthesia is generally preferred for cesarean delivery. 24,[11][12][13][14][33][34][35] Spinal anesthesia is superior to general anesthesia for neonatal acid-base status and Apgar score, 24,33,35,[11][12][13][14] and possibly also for neurobehavioral status and need for assisted ventilation. 35,36 Nonetheless, the results of our randomized controlled trials were not consistent, with some studies reporting no differences between general and neuraxial anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Past studies show that epidural or spinal anesthesia before cesarean has fewer side effects than other methods. However, general anesthesia is considered as a risk factor for jaundice (14). Based on the findings of another study, there is no relationship between the type of delivery and the severity of jaundice in newborns (15).…”
Section: Discussionmentioning
confidence: 99%